2018
DOI: 10.1145/3201783
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic Information, Plane Kakeya Sets, and Conditional Dimension

Abstract: We formulate the conditional Kolmogorov complexity of x given y at precision r, where x and y are points in Euclidean spaces and r is a natural number. We demonstrate the utility of this notion in two ways.1. We prove a point-to-set principle that enables one to use the (relativized, constructive) dimension of a single point in a set E in a Euclidean space to establish a lower bound on the (classical) Hausdorff dimension of E. We then use this principle, together with conditional Kolmogorov complexity in Eucli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…J. Lutz and N. Lutz gave computability theoretic proofs of both of these facts. They showed that the former corresponds to the existence of lines in all directions that contain no random points [25], and that the latter corresponds to the fact that for any random pair (a, x) ∈ R 2 , dim(x, ax + b) = 2 holds for all b ∈ R [26].…”
Section: Kakeya Sets and Generalized Furstenberg Setsmentioning
confidence: 99%
“…J. Lutz and N. Lutz gave computability theoretic proofs of both of these facts. They showed that the former corresponds to the existence of lines in all directions that contain no random points [25], and that the latter corresponds to the fact that for any random pair (a, x) ∈ R 2 , dim(x, ax + b) = 2 holds for all b ∈ R [26].…”
Section: Kakeya Sets and Generalized Furstenberg Setsmentioning
confidence: 99%
“…The most recent and powerful of these is the following, where we denote the classical Haus-dorff dimension of ⊆ ℝ by dim H ( ), and its classical packing dimension by dim p ( ). [19]).…”
Section: Some Applicationsmentioning
confidence: 99%
“…For example, Lutz and Stull [21] obtained a new lower bound on the Hausdorff dimension of generalized sets of Furstenberg type; Lutz [20] showed that a fundamental intersection formula, due in the Borel case to Kahane and Mattila, is true for arbitrary sets; and Lutz and Lutz [19] gave a new proof of the two-dimensional case (originally proved by Davies) of the well-known Kakeya conjecture, which states that, for all ≥ 2, if a subset of ℝ has lines of length 1 in all directions, then it has Hausdorff dimension .…”
Section: Theorem 14 (Lutz and Lutzmentioning
confidence: 99%
“…In computability theory (particularly in algorithmic randomness theory), it is usual to consider the algorithmic dimension (the algorithmic information density) of a point as an analogue of fractal dimension; see [7,Section 13]. The notions of Kolmogorov complexity and algorithmic dimension in a Euclidean space has been studied in [22][23][24][25], for instance. In this section, we compare our notion of topological dimension of points and the notions of effective fractal dimension of points.…”
Section: Effective Fractal Dimensionmentioning
confidence: 99%